Validation of a portable EMG device to assess muscle activity during free-living situations - Walters, T. J.; Kaschinske, K. A.; Strath, S. J.; Swartz, A. M.; Keenan, K. G. (Journal of Electromyography and Kinesiology, 2013)
Portable amplifiers that record electromyograms (EMGs) for longer than four hours are commonly priced over $20,000 USD. This cost, and the technical challenges associated with recording EMGs during free-living situations, typically restrict EMG use to laboratory settings. A low-cost system (µEMG; OT Bioelecttronica, 100€), using specialized concentric bipolar electrodes, has been developed specifically for free-living situations. The purpose of this study was to validate the µEMG system by comparing EMGs from µEMG with a laboratory-based alternative (Telemyo 900; Noraxon USA, Inc.). Surface EMGs from biceps brachii (BB) and tibialis anterior (TA) of ten subjects were recorded simultaneously with both systems as subjects performed maximal voluntary contractions (MVCs), submaximal contractions at 25%, 50%, and 75% MVC, seven simulated activities of daily living (ADLs), and >60 min of simulated free-living inside the laboratory. In general, EMG parameters (e.g., average full-wave rectified EMG amplitude) derived from both systems were not significantly different for all outcome variables, except there were small differences across systems in baseline noise and absolute EMG amplitudes during MVCs. These results suggest that µEMG is a valid approach to the long-term recording of EMG.